Time to act: a call for comprehensive responses to HIV in people who use drugs - Beyrer, C.; Malinowska-Sempruch, K.; Kamarulzaman, A.; Kazatchkine, M.; Sidibe, M.; Strathdee, S.A. (2010)
The published work on HIV in people who use drugs shows that the global burden of HIV infection in this group can he reduced. Concerted action by governments, multilateral organisations. health systems, and individuals could lead to enormous benefits for families, communities, and societies. We review the evidence and identify synergies between biomedical science, public health, and human rights. Cost-effective interventions, including needle and syringe exchange programmes, opioid substitution therapy, and expanded access to HIV treatment and care, are supported on public health and human rights grounds; however, only around 10 of people who use drugs worldwide are being reached. and far too many are imprisoned for minor offences or detained without trial. To change this situation will take commitment, advocacy, and political courage to advance the action agenda. Failure to do so will exacerbate the spread of HIV infection, undermine treatment programmes, and continue to expand prison populations with patients in need of care.